Navigating challenges, solutions and requirements in the provision of trauma care in conflict settings by humanitarian actors: a scoping literature review - Nikolaos Markou-Pappas; Luca Ragazzoni; Claudia Truppa; Flavio Salio; Francesco Barone-Adesi; Hamdi Lamine (Conflict and Health)
Abstract Background The evolving nature of irregular warfare and the increasingly frequent violations of human rights law and international humanitarian law pose unique challenges for humanitarian actors delivering trauma care in conflict settings. Methods A scoping review was conducted on PubMed, Scopus, and Web of Science and a web search (on Google, Google scholar and Bing) to analyze and review past humanitarian interventions offering trauma care in conflict settings. Relevant records were identified from scientific and grey literature. The thematic areas identified by the framework for a Public Health Emergency Operations Centre were used to facilitate the synthesis and analysis. Results Eleven records examining all phases of conflict identifying gaps throughout the continuum of care in the trauma systems were included. Challenges, solutions and requirements in transportation capacity, data collection methodologies, field coordination mechanisms, and rehabilitative care services were highlighted. Addressing the shortages in skilled healthcare workers, implementing quality improvement measures, and developing standardized training curricula were some of the requirements reported. Conclusions Our findings suggest that a multidimensional approach emphasizing strong coordination, with inclusive partnerships, is fundamental for effective trauma care systems in conflict zones. Key recommendations include robust medical transport, comprehensive healthcare training, preemptive mass casualty planning, standardized educational materials, continuous context reassessment, data protection, and improved transparency. These strategies could enhance trauma care interventions, ensuring they are effective, equitable, accountable, and sustainable.